Larangan Berbuat Zalim dalam Hadis,Implikasi Hukum Pidana & Perdata - Rina Mulyani; Tajul Arifin (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
The prohibition of committing injustice (zulm) is a fundamental principle in Islamic teachings that emphasizes justice as the foundation of social life. In various hadiths of the Prophet Muhammad (peace be upon him), injustice is strongly condemned as a violation of both divine rights and human rights. This article aims to discuss in depth the prohibition of zulm and explore its deeper implications in both criminal and civil law. Injustice is not only seen as an individual sin, but also as a breach of social justice and public order. Therefore, the command to avoid zulm, as conveyed in hadiths, goes beyond theological and moral dimensions, extending into concrete and applicable legal principles. Through a normative and juridical approach, this study seeks to demonstrate that the prohibition of injustice can serve as a foundation for developing a fair legal system that upholds individual rights. In the context of criminal law, acts of injustice often manifest as crimes requiring firm punishment to maintain social order. Meanwhile, in civil law, injustice appears in forms such as unlawful acts, breaches of contract, or violations of property rights, which demand compensation or restitution. This reflects the importance of integrating Islamic values in building a civilized and justice-oriented legal system.